The Effect of the Presence ofAudit Committees on Earnings Management in Morocco - El Haddad, Mohamed Yassine; Ez-Zarzari, Zakaria (European Scientific Journal, ESJ, 2017)
Our paper will try emphasizing the effect of the presence of audit committees on earnings management within the Moroccan context, and most specifically in the companies listed in the Casablanca stock exchange. We have adopted previous research embedded in the Dechow, Sloan and Sweeny (1995) model of earnings management that requires a maximum of 6 companies by sector, a condition that limited our sample to 27 companies dispatched only on 4 industry sectors. Given that the companies manipulate the accruals to show the increasing results or to maintain the stock price, the role of the audit committee is to ensure that this manipulation is to be reduced in order to provide investors with accurate information. In the Moroccan context, this reduction started appearing in 2014. The years 2011, 2012 and 2013 were marked by a preparation of implementation tools of these committees mainly the integration of independent administrators within the administrative boards. However, due to lack of data, this study might be limited given the fact that the year 2016, which represented a year where the listed companies should have created an audit committee, was not covered by our study.